2014
DOI: 10.1007/s10943-014-9915-2
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Indigenous Healing Among People with Psychiatric Disorders: Comparative Study of Arabic and Kurdish Ethnicities in Iraq

Abstract: Indigenous healing is commonly practiced in Middle East. Little is known about trends of indigenous therapies among patients with psychiatric disorders in Iraq. To determine and compare rates and predictors of indigenous healings by individuals with psychiatric disorders, and the practiced rituals among Arabic and Kurdish ethnicities in Iraq, patients aged 18 year and older attending outpatients in Erbil and Najaf were assessed for their prior contacts with indigenous healers. About 48.9 % had indigenous heale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Some of those continued to visit the faith healers routinely. A study performed in the region by Rahim et al[52] reported approximate results of 49%. While in a study conducted in India, they found that 8% of psychiatric patients consult a traditional faith healer at the beginning of their complaints[53].…”
Section: Discussionmentioning
confidence: 99%
“…Some of those continued to visit the faith healers routinely. A study performed in the region by Rahim et al[52] reported approximate results of 49%. While in a study conducted in India, they found that 8% of psychiatric patients consult a traditional faith healer at the beginning of their complaints[53].…”
Section: Discussionmentioning
confidence: 99%
“…There is an already established precedent for differences across the country regarding health and breastfeeding. Between the Kurdish region in the north and the south/central areas of Iraq, communities already interact with health systems and ideas of healing differently [30]. Studies of breastfeeding suggest that the south breastfeeds more than the northern governorates in the Kurdish region, with some variation in beliefs associated with breastfeeding [17,18], although the interpretation from these studies is limited by a large time difference between the two cross-sectional surveys.…”
Section: Discussionmentioning
confidence: 99%